2000
DOI: 10.1037/1099-9809.6.4.352
|View full text |Cite
|
Sign up to set email alerts
|

Hair-pulling in African Americans—Only your hairdresser knows for sure: An exploratory study.

Abstract: The authors examined whether African American hair care professionals saw individuals who met general criteria for trichotillomania, chronic hair pulling that results in significant hair loss. Thirty-eight African American hair care professionals and 1 Caucasian hair care professional were interviewed about their customers' hair-pulling behavior and condition of their hair. Sixteen African American hair care professionals saw 21 individuals who met general criteria for trichotillomania and reportedly perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Both Hollander and Cohen (1994) and Neighbors, Caldwell, Thompson, and Jackson (1994) suggested that African-Americans are less likely to seek help from traditional mental health providers and may instead be more likely to seek help from nonprofessional sources. Neal-Barnett, Ward-Brown, Mitchell, and Knownapple (2000) confirmed that in her sample, hair care professionals with a primarily African-American clientele did in fact provide assistance to their customers who chronically pulled out their hair. While this would contribute to the general underutilization of mental health service by African-American hair pullers, this does not preclude the possibility that other factors, such as resilience, may also operate.…”
Section: Discussionsupporting
confidence: 57%
“…Both Hollander and Cohen (1994) and Neighbors, Caldwell, Thompson, and Jackson (1994) suggested that African-Americans are less likely to seek help from traditional mental health providers and may instead be more likely to seek help from nonprofessional sources. Neal-Barnett, Ward-Brown, Mitchell, and Knownapple (2000) confirmed that in her sample, hair care professionals with a primarily African-American clientele did in fact provide assistance to their customers who chronically pulled out their hair. While this would contribute to the general underutilization of mental health service by African-American hair pullers, this does not preclude the possibility that other factors, such as resilience, may also operate.…”
Section: Discussionsupporting
confidence: 57%
“…The available literature on help-seeking behavior in minority communities (U.S. Department of Health and Human Services, 2001), suggests group differences in treatment received and treatment outcome. Although little is known about TTM and Latinos, data on African Americans (Neal-Barnett et al, 2000;Neal-Barnett & Stadulis, 2006) suggest higher perceptions of interference with daily functioning; therefore, we predict our minority sample will report higher interference scores than their Caucasian counterparts. For the purpose of this study, the term minority refers to African Americans and Latinos.…”
Section: Study's Rationale and Hypothesesmentioning
confidence: 92%
“…Unlike Caucasian hair, it is more difficult to pass a comb through wet Black hair than through dry Black hair (Franbourg, Hallegot, Baltenneck, Totain, & Leroy, 2003;Lindelof, Forslind, Hedblad, & Kaveus, 1988;Menkart, Wolfram, & Mao, 1966;Wolfram, 2001). This simple fact has sparked a 15-billion dollar hair care industry, influenced perceptions of Black and Latino attractiveness, and for some, has an emotional impact (Neal-Barnett et al, 2000;Neal-Barnett & Stadulis, 2006;Neal-Barnett, Statom, & Stadulis, in press). The difference in hair may affect pulling sites, with minorities being less likely to pull from the scalp than other sites.…”
Section: Study's Rationale and Hypothesesmentioning
confidence: 97%
See 2 more Smart Citations